Pengaruh Gaya Kepemimpinan Transformasional dan Komitmen Organisasi terhadap Kinerja Karyawan Pada Perusahaan Daerah Air Minum (PDAM) Kabupaten Bombana - Heri Prabowo; Almansyah Rundu Wonua; Andry Stepahnie Tititng (Transformasi: Journal of Economics and Business Management, 2023)
This study aims to determine: (1) The effect of transformational leadership style on employee performance (2) The effect of organizational commitment on employee performce.This study used a quantitative method approach with the study population being all employees of the Regional Drinking Water Company (PDAM) Bombana Regency with a total sample of 30 respondents. Instrument testing in this study used the Validity test and Reliability with SPSS 26.0. The research data analysis with a total 35 respondents technique used the structural equation modeling (SEM-PLS) method with SmartPLS 4.0. Based on the results of the study it is known that there is a positive and significant influence between the transformational leadership style variable on employee performance as indicated by the t-statistic value of 8,405 with a P-Values ​​of 0.000, while the variable Organizational Commitment has a positive and not significant effect on employee performance indicated by the t-value statistic of 0,142 with a P-Values ​​of 0.000.